Inhibitory interactions promote frequent bistability among competing bacteria - Erik S. Wright (Nature Portfolio, 2016)
We know little about the effect of relationships between species on the assembly of microbial communities. Here the authors map pairwise invasion relations between bacteria and find that instead of one strain dominating, inhibitory interactions mean that often neither strain can invade the other.